Postemergence Herbicide Tolerance of Buffalograss Entering Winter Dormancy. Issue 1 (20th December 2018) - Braun, Ross C.; Hoyle, Jared A.; Van Ryzin, Benjamin; Sousek, Matthew D.; Thompson, Cole S.
Abstract : Core Ideas: The fall is the optimum time to control winter annual and perennial broadleaf weeds. More information is needed on postemergence herbicide safety in the fall as buffalograss enters winter dormancy. Many postemergence herbicides can be safely applied to buffalograss entering winter dormancy with no effect on spring greenup. Turf managers have many herbicide and application timing options for weed control in buffalograss.